Epidemiological evaluation of cardiovascular risk factors in children living at the Far North - S. A. Tokarev; A. A. Buganov; E. L. Umanskaya (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To evaluate the prevalence of cardiovascular risk factors in children living at the Far North. Material and methods. The study involved 899 schoolchildren of Nadym City. Epidemiological, statistical, instrumental and laboratory methods were used. Main results. High prevalence of most risk factors was observed in the examined population. Children’s awareness on risk factors was assessed. The methods for complex prevention of cardiovascular risk factors in Circumpolar Region youngsters were defined. Conclusion. High prevalence of risk factors, observed in the trial, determines the need for widely applicable, population-level strategies aimed on improving children’s health. These strategies are included into the program of multi-factor cardiovascular prevention in Circumpolar Region.